Four new species of the spider genus Physocyclus Simon, 1893 (Araneae: Pholcidae) from Mexico, with updated taxonomic identification keys - Nolasco Samuel, Garduño; Valdez-Mondragón, Alejandro (European Journal of Taxonomy, 2022)
Four new species of the spider genus Physocyclus Simon, 1893 are described from Mexico. Two species are described based on male and female adult specimens: Physocyclus mariachi sp. nov. and P. sikuapu sp. nov. Two species are described only with female adult specimens: P. lyncis sp. nov. and P. pocamadre sp. nov. The biogeographical province with the highest diversity of species is the Balsas Depression, located in the Mexican Neotropic, with 12 species. Physocyclus lyncis sp. nov. belongs to the dugesi species group, whereas the other three new species belong to the globosus species group. The total number of species of Physocyclus is increased to 37, distributed in North America (mainly Mexico) and Central America, with one cosmopolitan species: P. globosus. Updated taxonomic identification keys for males and females are provided.